Tratamientos térmicos para el control de podredumbres en postcosecha de naranjas como alternativa a los fungicidas de síntesis - Cocco, Mariángeles (2022)
Consumer demand for postharvest treatments without agrochemicals has led to the investigation of alternatives such as heat treatments, which can affect other aspects of fruit quality1,2,3. For this reason, the objective of this work was evaluate these heat treatments in conditions that present rotten control in inoculated oranges without altering the quality of the fruits.